2017
DOI: 10.1103/physrevb.95.165433
|View full text |Cite
|
Sign up to set email alerts
|

How square ice helps lubrication

Abstract: In the context of friction we use atomistic molecular-dynamics simulations to investigate water confined between graphene sheets over a wide range of pressures. We find that thermal equilibration of the confined water is hindered at high pressures. We demonstrate that, under the right conditions, square ice can form in an asperity, and that it is similar to cubic ice VII and ice X. We simulate sliding of atomically flat graphite on the square ice and find extremely low friction due to structural superlubricity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In the limit t → ∞, we find from linear extrapolation of our data λ L (∞) = λ D (∞) := λ ≈ 0.492 (5). This compares well with the value of λ ≈ 0.47 reported earlier [43]. For any small but finite ε, D(x, t) would eventually saturate to the value 1, when de-correlation is complete (see Eq.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the limit t → ∞, we find from linear extrapolation of our data λ L (∞) = λ D (∞) := λ ≈ 0.492 (5). This compares well with the value of λ ≈ 0.47 reported earlier [43]. For any small but finite ε, D(x, t) would eventually saturate to the value 1, when de-correlation is complete (see Eq.…”
Section: Introductionsupporting
confidence: 91%
“…Denoting the two initial spin configurations discussed above by {S a x (t = 0)} and {S b x (t = 0)}, we can obtain a simpler expression as where S a x (t) · S b x (t) is the cross-correlator between the two copies. If the dynamics is chaotic, as is known to be in this classical spin-chain at infinite temperatures [43,44], we expect that for any x = 0, the above quantity, as a function of time, t, starts from the value 0 (when the spins of the two copies at a given x are perfectly correlated) and asymptotes to 1 (when they are completely de-correlated). Thus D(x, t) indeed measures the spatio-temporal evolution of de-correlation throughout the system.…”
Section: Introductionmentioning
confidence: 96%
“…We introduce a characteristic of the shape of the Lyapunov spectra, namely the "G-index", which exhibits a peak at the phase transition both as a function of temperature and energy, provided the order parameter is capable of sufficiently strong dynamic fluctuations. The present work builds on our earlier investigations of Lyapunov instabilities in classical spin lattices at infinite temperature 17,18 , where, in particular, we showed that the lattices are all chaotic with the exception of the Ising case.…”
Section: Introductionmentioning
confidence: 63%
“…This allows the system to stay in the ergodic regime not influenced by solitonic and breather-like solutions. (The experience with classical spin lattices [10,11] indicates that many-body classical systems are generically ergodic and chaotic at energies corresponding to sufficiently high temperatures. )…”
Section: Formulation Of the Problemmentioning
confidence: 99%